(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2023)
It is known that the Uzbek people have been in economic, political and cultural relations with other peoples throughout the historical periods. These contacts have a certain influence on the language of the people with whom they interact. As a result of interaction, changes occur in all parts of the language: phonetics, lexis, grammar, etc. Change and development in the language is strong in the lexicon of the language.